Boundary layers for the 3D primitive equations in a cube: The supercritical modes. (February 2016) - Hamouda, Makram; Jung, Chang-Yeol; Temam, Roger
Abstract: In this article we study the boundary layers for the viscous Linearized Primitive Equations (LPEs) when the viscosity is small. The LPEs are considered here in a cube. Besides the usual boundary layers that we analyze here too, corner layers due to the interaction between the different boundary layers are also studied.